Efektifitas Pelaksanaan Peran Kader Posyandu Harum Manis Kalimantan Barat - Agustine, Leony; Andri, Andri (JURNAL ADMINISTRASI KANTOR; Vol 11 No 2 (2023): Jurnal Administrasi Kantor (Desember 2023), 2023)
Posyandu has a very important role in efforts to improve the health of the Indonesian people, especially in reducing maternal and infant mortality rates and improving the nutritional status of children. This research aims to see the percentage of effectiveness of the role of posyandu cadres in their implementation at Harum Manis Posyandu, Sungai Raya Dalam District, Kubu Raya Regency, West Kalimantan. The method used in this research is a qualitative research data collection method from questionnaires given to mothers who were present during services at Posyandu Harum Manis. The effectiveness of the role of posyandu cadres at Harum Manis Posyandu for Data Collection on Toddlers, Weighing and Recording on Healthy Cards (KMS), Providing Additional Food, and Nutrition Counseling achieved high results of above 90%. However, the effectiveness of the role of Home Visits to Breastfeeding Mothers and Mothers with Toddlers and Being an Encouragement, Motivator and Community Instructor obtained low results.   Keywords: Posyandu, Role of Cadres, Effectiveness